Computer-aided reverse engineering system in the design and production of orthotic insole shoes for patients with diabetes. Issue 1 (1st January 2018) - Anggoro, Paulus Wisnu; Tauviqirrahman, M.; Jamari, J.; Bayuseno, A. P.; Bawono, B.; Avelina, M. M.
Abstract: Design and manufacturing strategies for custom orthotic insole shoes for patients with diabetes are presented in this paper. The computer-aided reverse engineering system (CARESystem) was applied for minimizing file errors generated by scanning a patient's foot. The digital data imaging and communication of medicine (DICOM) images were used for designing complex insole orthotics. The DICOM images obtained by HandySCANN 700 TM were then converted into a stereo lithography (STL) file (triangle-based data) format. The color map generated by VX Element and Geomagic software yielded an accurate and smooth STL data file of the patient's foot. A solid 3D model of orthotic shoe s (insole and outsole) was prepared using the curve-based surface modeling method (CBS model). The error of an image found in the 3D mesh STL file was then edited and smoothed, prior to the 3D prototype products being processed by 3D printers. The prototype of an orthotic shoe insole was fabricated by an adaptive manufacturing machine, the 3D printer EDEN350. Comparative analysis of dimensional data for the insole and outsole revealed that the average size of deviation was less than 1 mm (0.0135–0.0209 mm). Therefore, this method is highly promising to deliver custom orthotics with improved size, dimensional accuracy, and comfort.